Microarcsecond scintillation-induced variability (MASIV) survey of the northern sky - Jauncey, D.; Lovell, J.; Senkbeil, C.; Shabala, S.; Bignall, Hayley; Pursimo, T.; Ojha, R.; Dutka, M.; Macquart, Jean-Pierre; Rickett, B.J.; Kedziora-Chudczer, L. (Taylor & Francis, 2007)
We present the results of a large-scale 5-GHz Very Large Array (VLA) survey of the northern sky searching for sources that exhibit intraday variability (IDV). The observations were made over four epochs, each of 3 days in January, May and September 2002 and January 2003. The objective is to obtain a large sample of IDV sources in order to derive reliable statistics of the microarcsecond properties of the source population and the scattering properties of the interstellar medium.